EVALUATION OF THE PVD PERFORMANCE AT THE SECOND BANGKOK CHONBURI IDGHWAY (SBCH) PROJECT - D. T. Bergado; A. S. Balasubramaniam; I. A. Chishtr; T. Ruenkrairergsa; Y. Taesiri (Lowland Technology International, 1999)
The soft Bangkok clay foundation at the Second Bangkok Chonburi Highway Project (SBCH) was improved using prefabricated vertical drains (PVD). Monitoring instruments such as surface settlement plates, deep settlement plates, inclinometers and piezometers were installed in the subsoil in order to observe the deformation behavior of the embankments under loading. The Department of Highways, Thailand, arranged for the monitoring and documentation of the deformation behavior. These monitored records, supplemented with the laboratory test results, were analyzed in order to verify the in-situ horizontal coefficient of consolidation of the soil as well as the rate and amount of settlement. The maximum surface settlement was calculated using one-dimensional consolidation theory, Skernpton-Bjerrurn method, as well as Asaoka's method. In addition, a one-dimensional FEM computer software, capable of calculating the consolidation of multi-layered soil, named PVD-SD was also used successfully to predict the rate and amount of settlement. Finally, the monitored deformation behavior was compared with the predictions during the design stage of SBCH to evaluate the performance of PVD. The amount of settlement predicted by Asaoka's method was in excellent agreement with the observed values, whereas the one-dimensional consolidation method, Skempton-Bjerrurn method and the PVD-SD FEM method showed some overprediction. The PVD performance at SBCH Project confirmed and validated the ground improvement by preloading and drainage on soft Bangkok clay.